2015 Ieee Sensors 2015
DOI: 10.1109/icsens.2015.7370331
|View full text |Cite
|
Sign up to set email alerts
|

Development of new gas sensors based on oxidized galinstan

Abstract: For the first time, we have fabricated and tested conductometric sensors based on oxidized liquid galinstan towards NO 2 and NH 3 gases at low operating temperatures. Galinstan based films on silicon substrates have been studied with two different loadings. Surface morphology of the films was investigated by means of field emission scanning electron microscopy (FESEM). The sensor with higher galinstan loading showed a better sensitivity, which can be attributed to a higher surface area, as confirmed by SEM. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…From previous studies on liquid metal gallium–indium and galinstan, it was found that sonicating liquid metals in solution resulted in the formation of liquid metal micro-/nanodroplets that improved the performance in particular for galinstan in applications such as heavy metal ion sensing, gas sensing, photocatalysis, and heterogeneous catalysis . Therefore, the galvanic replacement of galinstan was also studied under sonication conditions.…”
Section: Resultsmentioning
confidence: 99%
“…From previous studies on liquid metal gallium–indium and galinstan, it was found that sonicating liquid metals in solution resulted in the formation of liquid metal micro-/nanodroplets that improved the performance in particular for galinstan in applications such as heavy metal ion sensing, gas sensing, photocatalysis, and heterogeneous catalysis . Therefore, the galvanic replacement of galinstan was also studied under sonication conditions.…”
Section: Resultsmentioning
confidence: 99%
“…From each channel, the velocimeter sequentially acquired the echo signals reflected by particles in the fluid to determine the distances between the particles and the transducer using the velocity of sound in the GaInSn. GaInSn oxidises readily in air 35 , which produces solid particles within it, thus eliminating the need to artificially suspend particles in the fluid 36 . The velocities of the particles were determined from their distances after successive pulse emissions.…”
Section: B Instrumentationmentioning
confidence: 99%
“…There is a significant range of overlap in the experimental rotation frequencies between m = 3 and 4, once again highlighting the multistability of the rotating waves resulting from differences in initial conditions. The intention of conducting experiments at Ha ∈ [30,35], where rotating waves with m = 3 was expected to be present throughout the interval, was to observe potential hysteresis in the rotation frequencies of the rotating waves depending on whether Ha was increased or decreased within the interval. However, we observed no hysteresis effect, as the rotation frequencies were almost indistinguishable from each other whether Ha was increased or decreased within the interval.…”
Section: Experiments With Varying Hamentioning
confidence: 99%
See 1 more Smart Citation
“…The growing demand for wearable devices and artificial body parts, including prosthetics and implantable device, has inspired research and the production of deformable electronics [ 36 , 37 ]. Many exciting and promising circuits [ 14 , 38 , 39 , 40 , 41 , 42 ] and electronic components [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] that can be bent (flexible) or elongated (stretchable) have been developed in recent years, although these applications are mainly at the laboratory stage. Figure 1 and Figure 2 are examples of flexible or stretchable applications based on Ga alloys.…”
Section: Properties Of Ga and Ga-based Alloysmentioning
confidence: 99%